Kalejdoskop: Poezja Krzysztofa Siwczyka jako przykład ewolucji zmiany poetyckiej na przełomie XX I XXI wieku - Walczak-Delanois, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article is an attempt to synthesize the evolution of Polish poetry after 1990. This symbolic date, associated with the official end of censorship and the symbolic beginning of the new time in Poland and last decade in the twentieth century, has been chosen as a border date. The author is interested in the process of creation and its mechanisms of describing the world in the work of Krzysztof Siwczyk. This poetry is important because it synthesizes the individual and collective experience and reflects the present.
The kaleidoscope. Krzysztof Siwczyk’s poetry as an example of the poetic evolution at the turn of the 20th and 21st centuries
Keywords: Krzysztof Siwczyk; poetry of the 20th and 21st century; evolution; synthesis; poezja XX i XXI wieku; ewolucja; synteza